2020
DOI: 10.1055/s-0040-1715605
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Variables Associated with Surgical Site Infection following the Management of Canine Cranial Cruciate Ligament Rupture with a Lateral Fabellotibial Suture

Abstract: Objectives This study investigated variables associated with surgical site infection (SSI) in dogs with cranial cruciate ligament rupture managed with stifle joint examination and lateral fabellotibial suture stabilization. Study Design A retrospective study of dogs that had stifle arthroscopy, stifle arthrotomy, or a combination of both, followed by lateral fabellotibial suture stabilization for cranial cruciate ligament rupture. All cases had a minimum follow-up of 90 days. Lameness grades were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 45 publications
(74 reference statements)
2
17
0
Order By: Relevance
“…Infection rates following TTA have been reported in 4.6 per cent to 15.4 per cent of cases, with between 1.3 per cent and 39 per cent of cases requiring implant removal for resolution (although the cage was not removed in the majority of cases) (Yap and others 2015, Hans and others 2017, Ferrell and others 2019). Similar infection rates of up to 14.5 per cent for CTCWO and 17.3 per cent for ECS have been reported, with the suture requiring removal in 53 per cent cases for resolution (Campbell and others 2016, Cox and others 2020).…”
Section: Postoperative Complicationssupporting
confidence: 68%
See 1 more Smart Citation
“…Infection rates following TTA have been reported in 4.6 per cent to 15.4 per cent of cases, with between 1.3 per cent and 39 per cent of cases requiring implant removal for resolution (although the cage was not removed in the majority of cases) (Yap and others 2015, Hans and others 2017, Ferrell and others 2019). Similar infection rates of up to 14.5 per cent for CTCWO and 17.3 per cent for ECS have been reported, with the suture requiring removal in 53 per cent cases for resolution (Campbell and others 2016, Cox and others 2020).…”
Section: Postoperative Complicationssupporting
confidence: 68%
“…Factors associated with significantly increased infection rates include increased bodyweight, being a GSD, undergoing meniscectomy, surgeon experience (<20 procedures), increased surgical and anaesthesia time, and induction with propofol (Fitzpatrick and Solano 2010, Yap and others 2015, Lopez and others 2018, Giannetto and Aktay 2019, Cox and others 2020). Although some authors reported a significantly reduced risk of infection and/or major complications when antibiotics were given postoperatively (Fitzpatrick and Solano 2010, Hans and others 2017), others reported no benefit (Yap and others 2015, Campbell and others 2016, Lopez and others 2018, Ferrell and others 2019, Cox and others 2020).…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Propofol use has been identified as a risk factor for surgical site infections in previous studies, 33,34 where it has been proposed that the lipid-based emulsion provides an environment suited for microbial growth and may contribute to surgical wound infection. In the present study, propofol administration was not associated with incisional complications.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that at least 53 large dogs and 159 small dogs were required (a total of 212 dogs), under the assumption that there was no difference in complications between the three procedures, 20% complications in the large dogs compared to 5% in the small dogs, with 80% power and a 95% confidence level for a two-tailed test. The predicted complication rates were based on previous studies (Casale & McCarthy 2009, Cook et al 2010a,b, Ritzo et al 2014, Cox et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The material used is typically a monofilament suture. Prior studies have shown that weight and age significantly influence the complication rates associated with this procedure (Casale & McCarthy 2009, Cox et al 2020. However, despite complications, acceptable outcomes have been reported for heavy dogs (>40 kg) especially when adequate physiotherapy is provided (Guénégo et al 2007, Jerre 2009.…”
Section: Introductionmentioning
confidence: 99%